The Sisciani in the Roman Empire - Šašel Kos, Marjeta (Studia Europaea Gnesnensia, 2017)
The article comments on residents of Siscia attested outside the city and its territory. It is based both on corpus of the Roman inscriptions from Siscia and inscriptions found elsewhere in the Roman Empire in which the Sisciani are documented. A few individuals, known from other provincial towns, were employed in municipal and provincial administration, while soldiers of various ranks predominate, legionaries as well as auxiliaries. Among them, soldiers serving in the Praetorian Guard are the best attested.